Audit Manajemen Atas Bahan Baku Untuk Meningkatkan Efisiensi dan Efektivitas CV.Ladjalani di Makassar - Subhan Subhan; Muhammad Reza Ramdani (P4M STIE Putra Bangsa, 2020)
This study examines the effectiveness of management audits of raw materials in the company CV. Ladjalani in Makassar. The purpose of this study to determine the activity of purchasing raw materials has been carried out efficiently and effectively. This research approach uses a descriptive quantitative approach. The method of data collection is done by observing directly the object of research and making direct observations, documenting archives or reports related to the activity of purchasing raw materials, questionnaires to find out the response to the researcher's questions on company activities. From the results of the study showed the activity of purchasing raw materials carried out by CV. Ladjalani is still inefficient and effective. This can occur due to waste of transportation costs or the cost of shipping raw materials. This waste occurs because the company establishes a policy on the purchasing department to purchase raw materials after getting an order. The company has not yet determined what frequency of purchasing the most economical raw materials.